Λ+c polarimetry using the dominant hadronic mode - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kubat, Jakub; Leverington, Blake; Marks, Jörg; et al. (Journal of high energy physics, 2023)
The polarimeter vector ﬁeld for multibody decays of a spin-half baryon is introduced as a generalisation of the baryon asymmetry parameters. Using a recent amplitude analysis of the Λ+c → pK−π+ decay performed at the LHCb experiment, we compute the distribution of the kinematic-dependent polarimeter vector for this process in the space of Mandelstam variables to express the polarised decay rate in a model-agnostic form. The obtained representation can facilitate polarisation measurements of the Λ+c baryon and eases inclusion of the Λ+c → pK−π+ decay mode in hadronic amplitude analyses.
LHCb Collaboration: R. Aaij, S. Bachmann, M. Borsato, R. Caspary, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, J. Kubat, B. Leverington, J. Marks, M.P. Morgenthaler, R. Skuza, D. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und 1043 weitere]
Im Text ist "+" hochgestellt und "c" tiefgestellt
Gesehen am 10.01.2024